2001
DOI: 10.1046/j.1365-2230.2001.00783.x
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of treatment of herpes labialis with 1072 nm narrow waveband light

Abstract: A randomized prospective double-blind study was performed to compare the efficacy of a single 5 min 1072 nm narrow waveband light application against topical aciclovir applied five times daily in the treatment of herpes labialis. Treatment was initiated within 36 h of the onset of symptoms and the end point was defined as the day that the crust was discarded leaving an uninterrupted underlying skin at the site of the cold sore. The results demonstrated that a single 5 min light treatment significantly reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
2
11
0
1
Order By: Relevance
“…On the other hand, one should bear in mind that the immune system is also under the influence of the laser 17,20 . Some authors suggest that immune cells against the HSV-1 virus are also proliferating, and they are active against a viral infection 21,22 . De Carvalho et al 21 used laser independently of the stage of the disease and the results showed the reduction of edema, and the size of the lesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, one should bear in mind that the immune system is also under the influence of the laser 17,20 . Some authors suggest that immune cells against the HSV-1 virus are also proliferating, and they are active against a viral infection 21,22 . De Carvalho et al 21 used laser independently of the stage of the disease and the results showed the reduction of edema, and the size of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Sa druge strane, ne treba zaboraviti da se imuni sistem takođe nalazi pod uticajem lasera 17,20 . Neki autori sugerišu da imune ćelije protiv HSV-1 virusa takođe proliferišu i aktivne su protiv virusne infekcije 21,22 . De Carvalho et al 21 .…”
Section: -10unclassified
“…The problems with conventional treatments have encouraged researchers to seek other treatment options for HSL. Light and laser therapies have attracted attention as a promising new treatment method for this condition . For example, the use of photodynamic therapy (PDT) using photosensitive agents (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In 2001, Dougal and Kelly (2) identified 1072 nm light as being effective in the treatment of cold sores which are known to be activated by ultraviolet light (3)(4)(5). In 2005, Bradford et al (6) demonstrated that pre-irradiating lymphocytes in culture with1072 nm light afforded them a degree of cytoprotection against subsequent ultraviolet toxicity which is known to adversely affect immune cell function (7,8).…”
Section: Introductionmentioning
confidence: 99%